Frequency Of Anti Double Stranded Dna Seropositivity In Patients With Lupus Nephritis - Hanan, Saad; Munib, Dr Syed; Sardar, Dr Waqas; Haseeb, Dr Abdul (Pakistan Journal of Kidney Diseases, 2025)
INTRODUCTION: Renal involvement affects approximately 38% of patients with systemic lupus erythematosus (SLE), with increased frequency and severity among African, Hispanic, and Asian populations. Lupus nephritis (LN) may present early or remain silent until progressing to end-stage renal disease (ESRD), contributing to significant morbidity. Variability in the prevalence of anti-double stranded DNA (anti-dsDNA) antibodies has been reported, and local data are scarce. This study aimed to assess the frequency of anti-dsDNA antibodies in patients with LN in our setting. OBJECTIVE: To determine the frequency of anti-dsDNA antibodies among patients with lupus nephritis. METHODS: A cross-sectional study was conducted at the Department of Nephrology, IKD, Peshawar, over six months (June–July 2020). A total of 139 patients meeting the American College of Rheumatology criteria for SLE and confirmed to have LN were evaluated. ELISA was used to detect anti-dsDNA antibodies. RESULTS: The mean age was 38 ± 9.91 years. Females comprised 66% of the cohort. Anti-dsDNA antibodies were present in 41% of patients. CONCLUSION: Anti-dsDNA antibodies were detected in 41% of patients with lupus nephritis, highlighting the importance of routine screening for early detection and management.